2007
DOI: 10.1111/j.1556-4029.2006.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Typing the 1.1 kb Control Region of Human Mitochondrial DNA in Japanese Individuals

Abstract: This study presents a reliable method that uses high-fidelity long-range PCR and optimized primers to assess polymorphism and to genotype human mitochondrial DNA (mtDNA). This method was used to analyze polymorphic sites in the human mtDNA control region, including hypervariable regions I, II, and III (HVI, HVII, and HVIII), from 124 unrelated Japanese individuals. In HVI, HVII, and HVIII, 80, 37, and 14 polymorphic sites were identified, respectively, excluding those in the homopolymeric cytosine stretch (C-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
(41 reference statements)
6
34
1
Order By: Relevance
“…In the present study, C-stretch length heteroplasmy was found at two positions within HVS-II. This finding agreed with that of several previous studies [23][24][25] . C-stretch length heteroplasmy increases the difficulties of DNA sequencing 19,20,36) and individual identification.…”
supporting
confidence: 94%
“…In the present study, C-stretch length heteroplasmy was found at two positions within HVS-II. This finding agreed with that of several previous studies [23][24][25] . C-stretch length heteroplasmy increases the difficulties of DNA sequencing 19,20,36) and individual identification.…”
supporting
confidence: 94%
“…e Sequence of the segment 16,195 is particularly shown in the parenthesis as described by Mabuchi et al (2007) except that the number of cytosines in the C-stretches are ignored and described as ''poly C. '' population. However, gene diversity among the Hokkaido Jomons (1.000 6 0.004) is higher than that among the native Siberians, suggesting that a certain level of genetic variation is maintained in the Hokkaido Jomon population studied.…”
Section: Genetic Characteristics Of the Hokkaido Jomon Mtdnasmentioning
confidence: 99%
“…Additional data obtained from previously published sources and used in this study included for mtDNA sequences: Chinese and Vietnamese (Oota et al, 2002); Japanese and Korean (Mabuchi et al, 2007); Itel'men and Koryak (Schurr et al, 1999); Bering Aleut (Zlojutro et al, 2006); Chukchi and Siberian Eskimo (Starikovskaya et al, 1998); Aleutian Aleut (Rubicz et al, 2003); Athabascan (Shields et al, 1993); Bella Coola and Haida ; West Greenland Eskimos (Saillard et al, 2000); Arsario, Ijka, Kogi, and Wayuú (Melton et al, 2007); and for Y chromosomes: Chinese, Japanese, Korean, Greenland Eskimo, and Amerindian (Willuweit et al, 2007); Aleutian Aleut (Rubicz, 2007); Apache, Dogrib, and Tanana (Malhi et al, 2008).…”
Section: Comparative Population Datamentioning
confidence: 99%